Social Capital and the Sustainability of KUD Business in Donggala District, Indonesia - Lutfi, Muhtar; Jokolelono, Eko; Muis, Armin; Sading, Yunus (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
This study aims to identify the social capital, co-production, and sustainability of KUD (Village Unit Cooperatives) business. It used descriptive research design using primary data obtained from KUD administrators and KUD members through the focus group discussion (FGD). It used FGD because in general KUD activities stopped after being affected by the natural disasters on September 28, 2018, and during the Covid 19 pandemic so that most of the KUD administrators and members were inactive and difficult to find. The findings of this study showed that (1) some KUD businesses have decreased the number of active KUD members, reduced income and SHU (net income) of KUD members due to the natural disasters that damage property and livelihoods of community members, especially members of KUD; (2) The active participation of KUD members has significantly decreased; (3) Only half of the number of KUDs are still running their activities; and (4) Overal, the social capital, co-production, and sustainability variables of KUD business are low.